Total dose radiation response of modified commercial silicon-on-insulator materials with nitrogen implanted buried oxide - 郑中山 刘忠立 于芳 李宁 (Chinese physics B, 2012)
Nitrogen ions of various doses are implanted into the buried oxide （BOX） of commercial silicon-on-insulator （SOI） materials, and subsequent annealings are carried out at various temperatures. The total dose radiation responses of the nitrogen-implanted SOI wafers are characterized by the high frequency capacitance-voltage （C-V） technique after irradi- ation using a Co-60 source. It is found that there exist relatively complex relationships between the radiation hardness of the nitrogen implanted BOX and the nitrogen implantation dose at different irradiation doses. The experimental results also suggest that a lower dose nitrogen implantation and a higher post-implantation annealing temperature are suitable for improving the radiation hardness of SOI wafer. Based on the measured C V data, secondary ion mass spectrometry （SIMS）, and Fourier transform infrared （FTIR） spectroscopy, the total dose responses of the nitrogen-implanted SOI wafers are discussed.